2019
DOI: 10.1136/bmjgast-2019-000288
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate transaminase to platelet ratio index (APRI) but not FIB-5 or FIB-4 is accurate in ruling out significant fibrosis in patients with non-alcoholic fatty liver disease (NAFLD) in an urban slum-dwelling population

Abstract: Background and aimsNon-invasive assessment of fibrosis in patients with non-alcoholic fatty liver disease (NAFLD) is challenging, especially in resource-limited settings. MR or transient elastography and many patented serum scores are costly and not widely available. There are limited data on accuracy of serum-based fibrosis scores in urban slum-dwelling population, which is a unique group due to its dietary habits and socioeconomic environment. We did this study to compare the accuracy of serum-based fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
5
21
0
2
Order By: Relevance
“…In this study, APRI proved vastly superior in diagnosing NASH and fibrosis in obese patients and performed better than Fib-4 and NAFLD fibrosis score. These findings concur with other studies, in which APRI also reached a higher accuracy than Fib-4 and NAFLD fibrosis score [ 32 , 33 ]. APRI furthermore has the obvious advantage to be easily assessable and moderate in costs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, APRI proved vastly superior in diagnosing NASH and fibrosis in obese patients and performed better than Fib-4 and NAFLD fibrosis score. These findings concur with other studies, in which APRI also reached a higher accuracy than Fib-4 and NAFLD fibrosis score [ 32 , 33 ]. APRI furthermore has the obvious advantage to be easily assessable and moderate in costs.…”
Section: Discussionsupporting
confidence: 93%
“…APRI furthermore has the obvious advantage to be easily assessable and moderate in costs. It therefore could also be successfully applied in a low-income population [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the best cut-off value for fibrosis detection by TE (LSM) vs. APRI score is 4.5 KPa, which fulfills the highest sensitivity, specificity, and accuracy (Table 4). This agrees with Kolhe et al who analyzed histological and clinical data of 100 consecutive urban slum-dwelling patients with NAFLD and showed that APRI had sensitivity, specificity, accuracy, PPV, NPV, and AUROC of 85.2%, 87.7%, 95%, 58.33%, 96.05%, and 0.95, respectively, with a statistically high significant correlation between APRI and biopsy-proven fibrosis [29].…”
Section: Discussionsupporting
confidence: 90%
“…The distinctive features of FIB-5, which is different from FIB-4, are inclusion of two variables (serum albumin and alkaline phosphatase [ALP]) and lower values are associated with a higher degree of fibrosis [ 8 ]. A previous study has reported that FIB-5 reflects the extent of liver fibrosis better than FIB-4 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%